Faith and History in the Old Testament. - MacKenzie, R. A. F. (University of Minnesota Press, 1963)
This absorbing and readable account of the religion of ancient Israel is presented against the background of other cultures of the time. Father MacKenzie traces the development of Israels belief and draws upon modern knowledge of the cultures of the anci.